HUBUNGAN ANTARA KEMAMPUAN PUKULAN DAN KELINCAHAN DENGAN KEMAMPUAN BERMAIN TENIS MEJA ATLET PEMULA PUTRI DI DIY - Verandita Rihtiana, Shafuuh Kemala Ria, dan Yuniaristi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
The research is aimed at revealing the relationship between the beating ability as wellas agility and the ability of playing table tennis among the female beginner athletes inYogyakarta Special Territory, and how much their contribution is.The population of this experimental research is all of the female athletes in DaerahIstimewa Yogyakarta with the use of survey method correlation. In this experiment tests areemployed, for example: the half of competition match to get the score of table tennis skill,test of beating balls with a time off using the method of beating the ball on the wall in 30seconds; and a side step test. The analysis to test the hypothesis is Product MomentCorrelation Analysis, Regression Analysis, and double regression analysis, with a confidenceinterval of 95%.Based on the result of the analysis it is revealed that (1) there is a significantly positiverelationship between the beating ability and table tennis ability among the female tabletennis athletes in Yogyakarta Special Territory (rXY= 0,817; p0,05 ); (2) there is a significantlypositive relationship between the agility and table tennis ability of the female table tennisathletes in Yogyakarta Special Territory (rXY= 0,787; p0,05). The beating ability contributeeffectively to the table tennis ability of the female table tennis athletes in Yogyakarta SpecialTerritory as much as 42.827; in addition agility contributes effectively as much as 33.744%.Key words: beating ability, agility, and table tennis ability